Web-Based Antam Gold Savings and Pawn Calculation Application: Case Study of a Gold Jewelry Manufacturing and Trading Company - Lindriani, Linda; Rinawati, Rinawati (Majalah Bisnis & IPTEK, 2023)
The demand for a user-friendly website that enables the withdrawal of funds from gold savings accounts at Pegadaian has experienced substantial growth amidst the ongoing epidemic. Due to its inherent value and stability, gold assumes particular significance in times of economic uncertainty, allowing individuals to liquidate their savings when necessary. The old approach entailed the manual input of customer information through Excel, which consequently required face-to-face interactions for payment processing. Nevertheless, a significant shift has transpired through the integration of an internet-based platform, facilitating the provision of personal data by clients and thereby establishing virtual profiles to conduct online transactions. Implementing this transformation has resulted in a more streamlined process, enhancing efficiency and improving accessibility for clients. The research methodology employed for this project is descriptive, encompassing direct field observations. Furthermore, the system employs the Object-Oriented Analysis and Design (OOAD) methodology to analyze and design the system. The main objective is to develop a system that streamlines the procedures of gold pawning and online savings for consumers. The data input process utilizes the PHP programming language, whereby the data is safely stored within a MySQL database. The integration of these elements guarantees a system that is both secure and efficient, effectively addressing the requirements of both customers and administrators.